Horizon scan of online plant trade reveals emerging invasive species and high-risk platforms - Jacob Maher; Oliver C. Stringham; John Virtue; Phillip Cassey (Biological Invasions, 2026)
Horticultural trade is the primary pathway for the introduction of invasive plant species. Increasingly, trade is conducted online via e-commerce platforms. We used automated web scraping to capture snapshots of the online plant trade in Australia across 11 e-commerce websites between 2020 and 2023, aiming to identify potentially invasive species for sale. We identified 3,822 species for sale, which we categorised based on their Australian regulatory, naturalisation and native status, as well as their evidence of impacts elsewhere. We found the sale of 194 ‘Priority’ species, which are already considered invasive in Australia; 544 ‘Attention’ species, which have naturalised in Australia; and 175 ‘Watch’ species that are invasive elsewhere in the world but have not yet naturalised in Australia. We further prioritised the 175 Watch species, highlighting four species ( Berberis thunbergii , Artemisia vulgaris , Rosa rugosa, and Elaeagnus angustifolia ) for immediate investigation based on global occupancy and abundance, climate suitability, propagule pressure, and evidence of impacts. We also evaluate invasion risk across e‑commerce platform types, finding that public online marketplaces list more plant taxa over time than nursery websites and that marketplaces and generalist nurseries tend to offer species with higher invasion risk than specialist nurseries. We recommend that this dataset is used as an aid for prioritising weed risk assessments by government authorities to prevent the establishment of new invasive plant species.

Who’s a pretty bird? Predicting the traded abundance of bird species in Australian online pet trade - Katherine G. W. Hill; Oliver C. Stringham; Stephanie Moncayo; Adam Toomes; Jonathan J. Tyler; Phillip Cassey; Steven Delean (Biological Invasions, 2024)

A snapshot of online wildlife trade: Australian e-commerce trade of native and non-native pets - Adam Toomes; Stephanie Moncayo; Oliver C. Stringham; Charlotte Lassaline; Lisa Wood; Mariah Millington; Charlotte Drake; Charlotte Jense; Ashley Allen; Katherine G.W. Hill; Pablo García-Díaz; Lewis Mitchell; et al. (Biological Conservation, 2023)

A guide to using the internet to monitor and quantify the wildlife trade - Oliver C. Stringham; Adam Toomes; Aurelie M. Kanishka; Lewis Mitchell; Sarah Heinrich; Joshua V. Ross; Phillip Cassey (Conservation Biology, 2021)
The unrivaled growth in e‐commerce of animals and plants presents an unprecedented opportunity to monitor wildlife trade to inform conservation, biosecurity, and law enforcement. Using the internet to quantify the scale of the wildlife trade (volume and frequency) is a relatively recent and rapidly developing approach that lacks an accessible framework for locating relevant websites and collecting data. We produced an accessible guide for internet‐based wildlife trade surveillance. We detailed a repeatable method involving a systematic internet search, with search engines, to locate relevant websites and content. For data collection, we highlight web‐scraping technology as an efficient way to collect data in an automated fashion at regularly timed intervals. Our guide is applicable to the multitude of trade‐based contexts because researchers can tailor search keywords for specific taxa or derived products and locations of interest. We provide information for working with the diversity of websites used in wildlife trade. For example, to locate relevant content on social media (e.g., posts or groups), each social media platform should be examined individually via the site's internal search engine. A key advantage of using the internet to study wildlife trade is the relative ease of access to an increasing amount of trade‐related data. However, not all wildlife trade occurs online and it may occur on unobservable sections of the internet.